The SAGE Handbook of Qualitative Business and Management Research Methods: Methods and Challenges - Cassell, Catherine (SAGE Publications Ltd, 2018)
The SAGE Handbook of Qualitative Business and Management Research Methods provides a state-of - the art overview of qualitative research methods in the business and management field. Bringing together a team of leading international researchers, the chapters offer a comprehensive overview of contemporary uses of methods in business & management disciplines, and the challenges that emerge in looking ahead to the future. The chapters in this volume have been arranged into three thematic parts: Part One: Contemporary methods: interviews, archival analysis, autoethnography, rhetoric, historical, stories and narratives, discourse analysis, group methods, sociomateriality, fiction, metaphors, dramaturgy, diary, shadowing and thematic analysis. Part Two: Visual methods: photographs, drawing, video, web images, semiotics and symbols, collages, documentaries. Part Three: Methodological developments: aesthetics and smell, fuzzy set comparative analysis, sewing quilts, netnography, ethnomusicality, software, ANTI-history, emotion, and pattern matching.